2001
DOI: 10.1177/002215540104900103
|View full text |Cite
|
Sign up to set email alerts
|

Lectin and Proteoglycan Histochemistry of Feline Pacinian Corpuscles

Abstract: S U M M A R YWe studied carbohydrate residues of glycoproteins and proteoglycans (PGs) in peritoneal Pacinian corpuscles of five adult cats. Terminal monosaccharides of glycoproteins and related polysaccharides were identified by lectin histochemistry and the PGs and glycosaminoglycans (GAGs) by specific antibodies. The most intensive lectin staining reactions indicated an abundance of glycoconjugates with terminal mannose (Man) or sialic acid residues, but no complex-type oligosaccharides were detected within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 26 publications
1
31
1
Order By: Relevance
“…The inner-core cells probably regulate the environmental surrounding of the axon through their function as a permeability barrier to ions and molecules (Bell et al 1994). Our histochemical findings, however, are somewhat different from those reported for Vater-Pacini corpuscles in the cat mesentery (Sames et al 2001), indicating that in the very large Vater-Pacini corpuscles of the raccoon forepaws, generally higher viscoelasticity and turgor may be present and have to be maintained. In this way, the whole system is better stabilized, and the large corpuscle remains in shape as a basic prerequisite for normal functioning.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…The inner-core cells probably regulate the environmental surrounding of the axon through their function as a permeability barrier to ions and molecules (Bell et al 1994). Our histochemical findings, however, are somewhat different from those reported for Vater-Pacini corpuscles in the cat mesentery (Sames et al 2001), indicating that in the very large Vater-Pacini corpuscles of the raccoon forepaws, generally higher viscoelasticity and turgor may be present and have to be maintained. In this way, the whole system is better stabilized, and the large corpuscle remains in shape as a basic prerequisite for normal functioning.…”
Section: Discussioncontrasting
confidence: 88%
“…The localization of all the terminal sugars indicates that O-linked high-molecularweight glycoproteins are present (Campbell 1999). Such type of glycoconjugates, which has the capability of water binding, may be specifically involved by its sialic acid component in the high viscocity of mucus-lining epithelia and, thus, generally in the viscoelastic properties of VaterPacini corpuscles (Sames et al 2001;Schauer 2004). The inner-core cells probably regulate the environmental surrounding of the axon through their function as a permeability barrier to ions and molecules (Bell et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the interlamellar spaces of the Pacinian corpuscles, the collagen that predominates in the outer core and external capsule was type II collagen, whereas the intermediate layer contains type V collagen (Pawson et al, 2000), the occurrence of decorin was observed in the same zones that contain type II collagen, and biglycan is restricted to the perineurial lamellae (Sames et al, 2001). The structures equivalent to the interlamellar collagen in Pacinian corpuscles have been analyzed in Meissner corpuscles of Macaca fuscata in which each corpuscle was entirely covered by a connective tissue capsule.…”
Section: The Extracellular Matrix and Thementioning
confidence: 99%
“…Since 1996, some reviews have been published that cover only partial aspects of the protein composition (Pawson et al, 2000;Johansson et al, 1999;Sames et al, 2001), and physiology (Johnson, 2002) of sensory corpuscles.…”
Section: Introductionmentioning
confidence: 99%